E-Government Optimization Strategy at The Ministry of Villages, Development of Disadvantaged Regions, and Transmigration - Hary Lasmana; Mani Festati Broto; Neneng Sri Rahayu (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
This paper focuses on the e-Government optimization at The Ministry of Villages, Development of Disadvantaged Regions, and Transmigration as eGovernment has become one of the strategic issues of Bureaucratic Reform. This study aims to identify the aspects of an organization’s environment, to analyze, and formulate strategies for e-government optimization. Evaluation tools use the design-reality gap analysis through seven dimensions of ITPOSMO to assess the level of eGovernment implementation success and identified the critical success and failure factors. Strategy formulation techniques are using three stages of the strategy formulation analytical framework. Results from this study, by measuring the design-reality gap across seven dimensions show eGovernment project is likely to partially fail unless action is taken to correct the gap. Using three stages of the strategy formulation analytical framework defines four strategy recommendations: forward integration, related diversification, backward integration, and product development. Findings from this research will serve to reduce the risks that may affect e-governance success in The Ministry of Villages, Development of Disadvantaged Regions, and Transmigration.